A cautionary tale about the potential impacts of gated culverts on fish passage restoration efforts. Issue 1 (2nd January 2019) - Baumgartner, Lee J.; Barwick, Matthew; Boys, Craig; Marsden, Tim; Martin, Kate; McPherson, Jarrod; Ning, Nathan; Phonekhampeng, Oudom; Robinson, Wayne; Singhanouvong, Douangkham; Stuart, Ivor; Thorncraft, Garry
Abstract: Combined fishway-culvert facilities are common in many tropical river systems in South East Asia, but little is known regarding their mutual passage effectiveness. We investigated the lateral passage of Lower Mekong Basin fish in Lao PDR, through a combined cone fishway-sluice gate culvert facility between the Mekong River and an adjacent wetland. Fish abundance and species richness were assessed during the beginning of the 2014 wet season at three locations within the fishway-culvert facility: (i) the bottom of the fishway (i.e. downstream end of the facility); (ii) the top of the fishway; and (iii) the top of the culvert (i.e. upstream end of the facility). Neither total fish abundance nor species richness varied significantly among the three locations while the wetland remained at levels where the culvert was only partially inundated and the culvert gate was fully open. However, part-way through the study the culvert became completely inundated and the culvert gate had to be partially closed to protect the downstream fishway. During this period of partial gate closure, fish abundance and species richness became significantly lower at the top of the culvert than at the two fishway locations. This suggests that sluice gate culverts are most effective at facilitating the lateral movement of fish in tropical river systems when they are designed and operated appropriately for the local hydrological conditions, and their gates remain fully open.